Comparative study of the effects of different glucocorticosteroids on eosinophil survival primed by cultured epithelial cell supernatants obtained from nasal mucosa and nasal polyps. Issue 3 (March 1995) - Mullol, J; Xaubet, A; López, E; Roca-Ferrer, J; Picado, C
Abstract : BACKGROUND--Supernatants from epithelial cell cultures enhance eosinophil survival in vitro, this effect being abrogated by previous incubation of eosinophils with glucocorticosteroids. This property has resulted in the development of an in vitro test to compare the potency of these drugs. A comparative study was performed with dexamethasone, methylprednisolone, deflazacort, and budesonide. METHODS--Human epithelial cell conditioned media (HECM) was generated from cultured epithelial cells obtained from healthy nasal mucosa and polyps. Eosinophils isolated from the peripheral blood were incubated with different corticosteroids for one hour before the addition of HECM. The inhibitory potency of the four steroids on the eosinophil survival index was compared using the concentration of steroid causing 50% inhibition (IC50). RESULTS--Eosinophil survival was increased by HECM from both healthy nasal mucosa and polyps. All four steroids blocked HECM-induced eosinophil survival in a dose-dependent manner. On healthy nasal mucosa methylprednisolone was the least potent (IC50 = 536 nM), deflazacort (IC50 = 264 nM) was twice as potent as methylprednisolone, while budesonide and dexamethasone were approximately nine times as potent (both IC50 = 58 nM). When potency was evaluated on the promoting effects of the HECM obtained from nasal polyps, the inhibitory potencies were lower and consequently the IC50 values were higher when compared with HECM generated from healthy nasal mucosa: methylprednisolone (IC50 = 546 nM), deflazacort (IC50 = 390 nM), dexamethasone (IC50 = 76 nM), and budesonide (IC50 = 78 nM). CONCLUSIONS--The potencies of glucocorticosteroids can be compared by evaluating their effects on the survival of eosinophils previously primed by supernatants obtained from epithelial cell culture. The different effects of steroids on eosinophils primed by HECM obtained from healthy nasal mucosa compared with HECM obtained from nasal polyps suggest that polyps might represent more active tissue which is relatively resistant to treatment with corticosteroids.